What's eating you? parasites, the inside story - Davies, Nicola 1958- (Candlewick Press, 2009)
Mites and lice, fleas, ticks and tapeworms -- most living creatures that have a habitat also are a habitat, including you (are you itchy yet?). Unwelcome guests -- parasites -- are everywhere, from the barnacles hitching a ride on a humpback whale's head to the tiny flies that control a bee's brain and make it literally dig its owns grave. Now an expert team returns for an in-depth look at how these insidious critters do it, whether it's leaping aboard moving targets or morphing their body shapes, and what their unwitting hosts have learned to do to fight back and reclaim their space
Includes index
Keywords: Parasites / Juvenile literature; Parasites; Parasites / Ouvrages pour la jeunesse; Juvenile works